Epidemiological profile of patients notified by suicide attempt from 2018 to 2021 in an Emergency Care Unit in the city of Cascavel/PR (Research, Society and Development, 2023)
Objective: To analyze the compulsory notification forms of patients over 18 years of age who were treated at the UPA Veneza, in Cascavel - PR, due to a suicide attempt, building the epidemiological profile of this population, and verifying whether there was an influence of the pandemic period caused by COVID-19. 19. Methods: Observational, cross-sectional, quantitative-descriptive study carried out by analyzing the compulsory notification forms of 458 patients notified of suicide attempts between January/2018 and December/2021 at UPA Jardim Veneza. Results: 458 notifications were reviewed. As for gender, the most reported gender both in the pre-pandemic and in the pandemic period was female, with 327 cases (71.4%), while 131 cases (28.6%) were male. The most notified age group throughout the period was between 18 and 29 years old, with 249 (54.3%) of the cases. As for race, in the pre-pandemic and pandemic period, the most reported race was white, with 304 (66.3%) cases. Regarding the area of ​​residence, the urban area predominated throughout the study period, totaling 437 cases (95.4%). Occurrences of previous suicide attempts were found in 271 (59.1%) of the notifications. The most used means to cause self-injury, both in the pre-pandemic and in the pandemic period, was poisoning, with 332 (72.4%) of the cases. Conclusion: Patients who had compulsory notification forms filled out due to suicide attempts followed the same pattern of epidemiological profile throughout the study period, concluding that there was no significant influence of the pandemic on the epidemiological profile of these patients.